1) 1-вариант, если выражение имеет такой вид: (17/8х)=-1-(3/4) (17/8х)=-(1×4+3)/4 (17/8х)=-(7/4) 56х=-68|÷56 х=-(68/56) х=-1(12/56)=-1(3/16)~-1,214286 2-вариант, если выражение имеет такой вид: (17/8)х=-1-(3/4) (17/8)х=-(7/4)|÷(17/8) х=-(7×4×2)/(4×17) х=-(14/17)~-0,82353
1) 1-вариант, если выражение имеет такой вид: (17/8х)=-1-(3/4) (17/8х)=-(1×4+3)/4 (17/8х)=-(7/4) 56х=-68|÷56 х=-(68/56) х=-1(12/56)=-1(3/16)~-1,214286 2-вариант, если выражение имеет такой вид: (17/8)х=-1-(3/4) (17/8)х=-(7/4)|÷(17/8) х=-(7×4×2)/(4×17) х=-(14/17)~-0,82353
x=-0,87
x + 3,4 = 2,6
x=-0,8
x – 2,7 = -5,3
x=-2,6
x – 3,7 = -6,3
x=-2,6
x + 2,3 = 1,7
x=-0,6